No clinically relevant electrocardiogram effects in a randomized TQT study of single therapeutic/supratherapeutic rimegepant doses in healthy adults - Rajinder Bhardwaj; Michael S. Hanna; Beth A. Morris; Kyle T. Matschke; Richard Bertz; Robert S. Croop; Jing Liu (Wiley, 2024)
Abstract A single‐center, phase I, partially double‐blind (double‐blind regarding doses of rimegepant and placebo, and open label with respect to moxifloxacin), randomized, 12‐sequence, four‐period crossover study of therapeutic (75 mg) and supratherapeutic (300 mg) doses of rimegepant with placebo and moxifloxacin (400 mg) controls was designed to evaluate drug effect on the Fridericia corrected QT (QTcF) interval in healthy fasted adults. A total of 38 participants were randomized and dosed in the study. Electrocardiogram (ECG) data were available from 37 participants in the rimegepant 75‐mg group, 38 participants in the rimegepant 300‐mg group, and 36 participants in the moxifloxacin and placebo groups. Both the 75‐ and 300‐mg doses of rimegepant had no clinically relevant effect on ECG parameters, including QTcF, heart rate, PR and QRS interval, T‐wave morphology, and U‐wave presence. All upper 90% confidence intervals for the QTcF effect with rimegepant were less than or equal to 4.69 ms, well below the 10‐ms threshold for potential clinical significance. Assay sensitivity was demonstrated by the QT effect of moxifloxacin. Using both by‐timepoint and concentration‐QTc analysis, a placebo‐corrected change‐from‐baseline QTcF greater than 10 ms could be excluded for rimegepant plasma concentrations up to ~10,000 ng/mL, representing concentrations at least 10.8‐fold the maximum observed concentration of the 75‐mg therapeutic dose of rimegepant.